2022
DOI: 10.1111/myc.13433
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19‐associated aspergillosis in a Brazilian referral centre: Diagnosis, risk factors and outcomes

Abstract: Background COVID‐19 patients on mechanical ventilation are at risk to develop invasive aspergillosis. To provide additional data regarding this intriguing entity, we conducted a retrospective study describing risk factors, radiology and prognosis of this emerging entity in a Brazilian referral centre. Methods This retrospective study included intubated (≥18 years) patients with COVID‐19 admitted from April 2020 until July 2021 that had bronchoscopy to investigate pulmonary co‐infections. COVID‐19‐associated as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 33 publications
1
12
1
Order By: Relevance
“…17,20,24,25 However, despite higher mortality with CAPA in COVID-19 patients in Brazil, no significant difference was observed in comparison with non-CAPA patients. 19 To the best of our knowledge, our study is the one of the few and the largest from LMICs, from an area with a high fungal disease burden with limited resources for diagnosis. 26 Moreover, our study evaluated the impact of CAPA on patient outcomes.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…17,20,24,25 However, despite higher mortality with CAPA in COVID-19 patients in Brazil, no significant difference was observed in comparison with non-CAPA patients. 19 To the best of our knowledge, our study is the one of the few and the largest from LMICs, from an area with a high fungal disease burden with limited resources for diagnosis. 26 Moreover, our study evaluated the impact of CAPA on patient outcomes.…”
Section: Discussionmentioning
confidence: 93%
“… 17 Most studies exploring CAPA risk factors have either included all intubated patients or critically ill patients, hence excluding possibility of analysing this as a risk factor for CAPA. 18 , 19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 14 studies reporting the use of isavuconazole for CAPA, as shown in Table 2 [ 3 , 5 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 ]. In these 14 studies, 235 of 275 CAPA patients (85%) received antifungal treatment, whereas 40 patients did not receive any type of antifungal treatment.…”
Section: Isavuconazole In Capamentioning
confidence: 99%
“…In a report from Brazil, 12 of 14 ICU CAPA cases received antifungal treatment, mainly voriconazole monotherapy (67%), while in 1 case L-AmB was changed to isavuconazole due to chronic renal failure [ 55 ]. On the contrary, in two small studies from Greece and Spain, isavuconazole monotherapy was the most frequently used (approximately 80% of patients) [ 50 , 51 ].…”
Section: Isavuconazole In Capamentioning
confidence: 99%